Sistem Informasi Pencegahan Korupsi Bantuan Sosial (Si Pansos) di Indonesia: Rumusan Konsep dan Pengaturan - Alfedo, Juan Maulana; Nur Azmi, Rama Halim (Integritas : Jurnal Antikorupsi, 2020)
The Covid-19 pandemic that occurred in almost all countries has caused an economic crisis for various countries, including Indonesia. To maintain the level of consumption and minimize the increase in poverty due to the pandemic, the government provides social assistance for people who are affected economically. However, social assistance which is supposed to be a means of stabilizing the people’s economy is misused. Various problems occurred in the distribution of social assistance, starting from the unqualified recipient chosen, the reduced value of the cash, corruption, and embezzlement. The author designed Si Pansos as an electronic-based information system website containing information management, distribution, and reports regarding to the social assistance. Si Pansos is an application employing the principles of accountability and transparency in public services. The method used in this paper is a normative juridical approach to legislation, a case approach, and a conceptual approach.